The University of the Philippines Filipinana Dance Group in concert [videorecording] Kayumanggi at iba pa, held at the University Theater on February 23, 1993. (Quezon City U.P. Filipiniana Dance Group, 1993)
A dance presentation of the U.P. Filipiniana Dance Group.
A Tribu (Dances of the Cultural Communities). Dugsu (Bukidnon tribe of Mindanao) -- War dance (Bontoc tribe) -- Madal T'boli (T'boli tribe of Upland Mindanao) -- Kuntao (Tausogs) -- Pangalitawo (Subanon) -- Karegtek (Benguet) -- Uya-oy (Ifugaos) -- Kampalong-malong (Muslim) -- Singkil (Muslim Royalty) -- B. Kasalan (Spanish Influenced Dances). Malagueno -- Jota Bicolana -- Miligoy de Cebu -- Habanera de Sollera -- Jota Sevillana -- C. Sa Aming Nayon (Dances from Rural Areas). Planting Rice -- Pandanggo sa Tapis -- Bati -- Kuratsa -- Subli -- Tinikling -- Sayaw sa Bangko -- Pandanggo sa Ilaw -- B. Modern Dances. R U OK -- Ngayon lang -- Dapit Hapon -- Pagdiriwang
VHS.
Keywords: University of the Philippines Filipiniana Dance Group; Dancing -- Philippines; Human kinetics